Analisis Aktivitas Harian Rusa Sambar (Cervus unicolor) di Kandang Demplot Litbang Rusa BP2LHK Aek Nauli Kabupaten Simalungun Sumatera Utara - Tri Astuti; Tioner Purba; Riski Kurniawan (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2026)
The sambar deer (Cervus unicolor) is a species that thrives in Asia. In Indonesia, sambar deer are a protected species. Exploitation and poaching have impacted their existence. One effort is to conduct captive breeding (ex situ conservation) by constructing enclosures (demonstration plots). The objectives of this study were: to determine the daily activity of sambar deer, to determine the percentage of daily activity, and to compare daytime and nighttime activity. Data collection of sambar deer activity was conducted using focal animal sampling and observation methods. Observations showed that sambar deer (Cervus unicolor) in the Deer Research and Development Enclosure, BP2LHK Aek Nauli, Simalungun Regency, engaged in various activities, including movement, resting, sleeping, eating, socializing, and other activities (grooming, defecation, urination, and additional activities observed in the field, such as nursing (for mothers) and suckling (for young).The research results showed that the sambar deer in the enclosure engaged in activities such as resting (54.98%), eating (22.85%), moving (10.14%), sleeping (8.99%), other (3.02%), and social (0%). Comparison of sambar deer activity between daytime and nighttime activities: Moving 54.10% - 45.80%, more active during the day, Resting 50.12% - 49.81%, Sleeping 7.53% - 92.46%, greater sleep activity at night, Eating 63.95% - 36.04%, Eating activity predominates during the day, Social (0), Data shows that the deer do not engage in any social activity at all, Other 54.02% - 45.97%